Basic chronobiology: what do sleep physicians need to know? - Zaki, Nevin F.W.; Spence, David Warren; Subramanian, Perumal; Bharti, Vijay K; Karthikeyan, Ramanujam; BaHammam, Ahmed Salem; Pandi-Perumal, Seithikurippu R (Sleep Science, 2020)
Sleep is an essential physiological process, which profoundly affects a wide range of biological activities. It is now known that sleep supports myriad vital functions in the central nervous system. This includes neural plasticity, learning, memory, cognition and emotional regulation. Additionally, it affects basic processes such as cardiovascular, immunological and metabolic activity. Evidence from multiple lines of research has thus shown that good quality of sleep is essential for both survival and optimal functioning of life. Considerable evidence also supports the conclusion that even minimal dysfunctions in circadian regulation can significantly disrupt sleep and broadly affect body physiology. As a consequence, it is now appreciated that the therapy of sleep disorders is more complex than was once thought. At present, several clinical disciplines have recognized the significance of the biological clock in health and illness, and are incorporating this knowledge into treatment programs. Recent decades have seen the emergence of chronotherapies, i.e., treatment strategies that are aimed at producing adjustments in the circadian clock. The final objective of these approaches is to affect basic cellular and physiological processes, which in turn may be at the root of disorders such as physiological aging, immune functioning, metabolic activity, and psychiatric disturbance. It is suggested that the integration of chronobiological perspectives into many mainstream medical disciplines would be of significant benefit, both for the reduction of the prevalence of diseases and their treatment. This review considers the physiology of sleep and the importance of timekeeping mechanisms in the regulation of overall health.
Keywords: Chronobiology Discipline; Chronotherapy; Circadian Clocks; Clock Genes; Sleep; Sleep Medicine